Reconceptualising Agency and Childhood New perspectives in Childhood Studies - Esser, Florian; Baader, Meike S.; Betz, Tanja; Hungerland, Beatrice (Routledge Research in Education, 2016)
By regarding children as actors and conducting empirical research on children's agency, Childhood Studies have gained significant influence on a wide range of different academic disciplines. This has made agency one of the key concepts of Childhood Studies, with articles on the subject featured in handbooks and encyclopaedias. Reconceptualising Agency and Childhood is the first collection devoted to the central concept of agency in Childhood Studies. With contributions from experts in the field, the chapters cover theoretical, practical, historical, transnational and institutional dimensions of agency, rekindling discussion and introducing fundamental and contemporary sociological perspectives to the field of research. Particular attention is paid to connecting agency in the social sciences with Childhood Studies, considering both the theoretical foundations and the practice of research into agency. Empirical case studies are also explored, which focus upon child protection, schools and childcare at a variety of institutions worldwide. This book is an essential reference for students and scholars of Childhood Studies, and is also relevant to Sociology, Social Work, Education, Early Childhood Education and Care (ECEC) and Geography. Chapter 6 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138854192_oachapter6.pdf